Synthesis and Biological Evaluation of Some 1,8-Naphthalimide-Acridinyl Hybrids - Rui Chen; Caiying Yuan; Yogini Jaiswal; Lini Huo; Dianpeng Li; Leonard Williams; Jing Zhong; Yan Liang (Journal of Chemistry)
In the present study, the synthesis of three 1,8-naphthalimide-acridinyl hybrids (2a, 2b, and 5b) using N-amido-1,8-naphthalimides (1 and 4) and acridinyl isothiocyanates is reported. The newly synthesized hybrids were evaluated for their anticancer activity in six human cancer cell lines (HL-60, MT-4, HepG2, HeLa, SK-OV-3, and MCF-7). Their inhibition activity against DNA-topoisomerase I (Topo I) and Electrophorus electricus acetylcholinesterase (AChE) was also studied. The results indicate that 2b displayed good cytotoxicity for MT-4, HepG2, HeLa, and SK-OV-3 with the IC50 values of 14.66 ± 0.31, 27.32 ± 2.67, 17.51 ± 0.34, and 32.26 ± 1.74 μM, respectively. All compounds, especially 2b, exhibited obvious bands corresponding to DNA fragments at 0.5 mM concentration, further confirming the pharmacological mechanism related to the Topo I inhibitory activities. In addition, compound 2a exhibited higher inhibition activity against AChE than 2b and 5b, with IC50 values of 0.32 ± 0.04 mM, and the acridinyl ring may contribute to the activity of 2a.